Population-based evaluation of the ' LiveLighter' healthy weight and lifestyle mass media campaign. Issue 2 (8th March 2016) - Morley, B.; Niven, P.; Dixon, H.; Swanson, M.; Szybiak, M.; Shilton, T.; Pratt, I. S.; Slevin, T.; Hill, D.; Wakefield, M.
Abstract: The Western Australian (WA) 'LiveLighter' (LL) mass media campaign ran during June–August and September–October 2012. The principal campaign ad graphically depicts visceral fat of an overweight individual ('why' change message), whereas supporting ads demonstrate simple changes to increase activity and eat healthier ('how' to change message). Cross-sectional surveys among population samples aged 25–49 were undertaken pre-campaign ( N = 2012) and following the two media waves ( N = 2005 and N = 2009) in the intervention (WA) and comparison state (Victoria) to estimate the population impact of LL. Campaign awareness was 54% after the first media wave and overweight adults were more likely to recall LL and perceive it as personally relevant. Recall was also higher among parents, but equal between socio-economic groups. The 'why' message about health-harms of overweight rated higher than 'how' messages about lifestyle change, on perceived message effectiveness which is predictive of health-related intention and behaviour change. State-by-time interactions showed population-level increases in self-referent thoughts about the health-harms of overweight ( P < 0.05) and physical activity intentions ( P < 0.05). Endorsement of stereotypes of overweight individuals did not increase after LL aired. LL was associated with some population-level improvements in proximal and intermediate markers of campaign impact. However, sustained campaign activity will be needed to impact behaviour.